Relation of Apathy to Motor and Non-motor Findings in Parkinson’s Disease - Melek Gürbüz; Gönül Akdağ; Özge Arıcı Düz; Feriha Özer; Özlem Çokar; Lütfü Hanoğlu (Haseki Tıp Bülteni, 2019)

(untitled)
Aim:It has been shown that motor symptoms, as well as non-motor symptoms, significantly affect the quality of life of patients with idiopathic Parkinson’s disease. In our study, the association of apathy, one of the NMS, with motor and non-motor symptoms was investigated.Methods:Patients with stage 1-3 IPH according to the Hoehn-Yahr Scale (H&Y) were included in the study. Patients who received dementia diagnosis according to the DSM IV criteria were excluded from the study. The patients were evaluated using the Unified Parkinson’s Disease Rating Scale (UPDRS), non-motor symptoms Questionnaire (NMSQ), Geriatric Depression Scale (GDS), and the revised diagnostic criteria for apathy.Results:Apathy was found in 26 of 68 patients who were included in the study. Patients with and without apathy were compared in terms of age, clinical and demographic characteristics, L-dopa equivalent doses, depression, and NMSQ scores. The group of patients with apathy consisted of nine females and 17 males and the mean age was 64.3±7.7 years. The non-apathy group included 25 females and 17 males and the mean age was 66.8±9.1 years. There was no statistically significant difference between the groups in terms of age, education, age at onset, duration of illness and L-dopa equivalent doses. The male-to-female ratio was significantly higher in the apathy group. The mean GDS and NMSQ scores in the apathy group were significantly higher than in the non-apathy group. There was a statistically significant difference between the groups in H&Y stage and total UPDRS and subscales scores. It was noteworthy that the rate of stage 3 patients was higher in the group of patients with apathy. The number of patients having bradykinesia in the apathy group and the number of patients having tremor in the group without apathy was higher.Conclusion:Our study showed that apathy, one of the non-motor symptoms, was more prominent in male gender, associated with UPDRS scores, clinical stage and bradykinesia, and accompanied by depression.